INDEPENDENT REVIEW OF RESEARCH PROPOSALS FROM ETHICAL POINT OF VIEW IN PAKISTAN - Salim, Mohammad; Hamid, Saima (Journal of Ayub Medical College Abbottabad, 2018)
Background: Ethics is a part of subject philosophy and gained importance in research after the Nuremberg Code that led to Helsinki’s Declaration on research ethics. In most developed countries stringent measures are taken to implement ethics in research. Awareness is on the rise in developing countries too. Methods: This cross-sectional part of mixed methods design of study is part of a PhD thesis. Data was collected from medical institutions including medical colleges, medical universities, dental colleges, and teaching hospitals of Pakistan. Questionnaires were developed, and final version was adopted after pretesting. Questionnaires were sent via registered post. Results: A total of 78 institutions responded. Out of 78, 48 (61.5%) were in public sector and 30(38.5%) in private sector. Seventy-four (94%) had institutional review boards. The numbers of members ranged from 1 to 15 with 40(54%) having number of members from 3 to 7. Out of 74 with IRBs, 17(23%) had members from community, 11(15%) had religious scholars and 8(11%) had members from legal background. Sixty-four (86.5%) responded that they had time frames for research proposal processing that ranged from one to 26 weeks (6.2±5.6) Conclusion: It is concluded that most of the medical institutions where research is conducted and approved through deficient research ethical boards in terms of their constitution. Research ethics is not a priority area for most of the institutions. Representation of society at large is missing. National action is required at government level. Keywords: Institutional Review Boards; Research Ethics; Ethics Committees; Constitution of IRBs